2014
DOI: 10.1186/1471-2164-15-578
|View full text |Cite
|
Sign up to set email alerts
|

Identification of cucurbitacins and assembly of a draft genome for Aquilaria agallocha

Abstract: BackgroundAgarwood is derived from Aquilaria trees, the trade of which has come under strict control with a listing in Appendix II of the Convention on International Trade in Endangered Species of Wild Fauna and Flora. Many secondary metabolites of agarwood are known to have medicinal value to humans, including compounds that have been shown to elicit sedative effects and exhibit anti-cancer properties. However, little is known about the genome, transcriptome, and the biosynthetic pathways responsible for prod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(36 citation statements)
references
References 34 publications
1
31
0
Order By: Relevance
“…Cucurbitacin A (C 32 H 46 O 8 ) and cucurbitacin B (C 32 H 46 O 9 ) are tetracyclic triterpenoids (Chen et al 2005), synthesised by the mevalonic acid pathway (Chen et al 2014). The water-soluble cucurbitacin A is unstable and oxidises to cucumin (C 27 H 40 O 9 ) and leptodermin (C 27 H 38 O 8 ), which had been shown to have both insect repellent and insecticidal activities (Damalas 2011;Gobinda et al 2014).…”
Section: Introductionmentioning
confidence: 98%
“…Cucurbitacin A (C 32 H 46 O 8 ) and cucurbitacin B (C 32 H 46 O 9 ) are tetracyclic triterpenoids (Chen et al 2005), synthesised by the mevalonic acid pathway (Chen et al 2014). The water-soluble cucurbitacin A is unstable and oxidises to cucumin (C 27 H 40 O 9 ) and leptodermin (C 27 H 38 O 8 ), which had been shown to have both insect repellent and insecticidal activities (Damalas 2011;Gobinda et al 2014).…”
Section: Introductionmentioning
confidence: 98%
“…And the genes related to terpenoid biosynthesis in wounded stems of A. malaccensis was also investigated by transcriptome sequencing, which demonstrated the upregulation of the expression of genes involved in terpenoid biosynthesis after wounding . The draft genome of A. agallocha was used to identify the genes related to cucurbitacin biosynthesis, which is the first report on the draft genome for any species of Aquilaria …”
Section: Discussionmentioning
confidence: 99%
“…In a more recent research, in vitro materials from Aquilaria agallocha were found to contain abundant amounts of triterpene cucurbitacin I and E (Chen et al 2014 ). Although the true identity of the A. agallocha species is dubious as it is a synonym of Aquilaria malaccensis , nevertheless the assembled draft of its genome contributes to sequence information on Aquilaria , which is currently lacking.…”
Section: Enzymes In Triterpene Synthesismentioning
confidence: 97%